Prospects of herbivore egg‐killing plant defenses for sustainable crop protection. Issue 19 (7th September 2016) - Fatouros, Nina E.; Cusumano, Antonino; Danchin, Etienne G.J.; Colazza, Stefano
Abstract: Due to a growing demand of food production worldwide, new strategies are suggested to allow for sustainable production of food with minimal effects on natural resources. A promising alternative to the application of chemical pesticides is the implementation of crops resistant to insect pests. Plants produce compounds that are harmful to a wide range of attackers, including insect pests; thus, exploitation of their natural defense system can be the key for the development of pest‐resistant crops. Interestingly, some plants possess a unique first line of defense that eliminates the enemy before it becomes destructive: egg‐killing. Insect eggs can trigger (1) direct defenses, mostly including plant cell tissue growth or cell death that lead to eggs desiccating, being crushed or falling off the plant or (2) indirect defenses, plant chemical cues recruiting natural enemies that kill the egg or hatching larvae (parasitoids). The consequences of plant responses to eggs are that insect larvae do not hatch or that they are impeded in development, and damage to the plant is reduced. Here, we provide an overview on the ubiquity and evolutionary history of egg‐killing traits within the plant kingdom including crops. Up to now, little is known on the mechanisms and on the genetic basis of egg‐killing traits. Making use of egg‐killing defense traits in crops is a promising new way to sustainably reduce losses of crop yield. We provide suggestions for new breeding strategies to grow egg‐killing crops and improve biological control. Abstract : Exploiting egg‐killing defense traits should be promising to reduce crop losses in future. However, little is known on the mechanisms and on the genetic basis of egg‐killing traits. In our review article, we address three main topics: (1) the phylogeny and ubiquity of plants expressing insect egg‐killing defenses, (2) mechanisms underlying and to be addressed in egg‐killing traits, and (3) the use for integrated pest management.